Impacto de la renta de recursos naturales en la corrupción de Ecuador periodo 1990-2021: mediante un Modelo Econométrico de Series de Tiempo - Villa López, Ana Paula (2024)
Corruption is a phenomenon that has been present in society since ancient times. Corruption costs around 2.6 trillion dollars, that is, 5% of global GDP. Although there are several reasons behind this problem, the rent generated by natural resources attracts rent-seeking for personal benefit. The objective of this research is to analyze the impact between the income of natural resources and the levels of corruption in Ecuador during the period 1990-2021, using statistical and econometric techniques, to provide recommendations to mitigate the effects of corruption in the management of natural resources. In this context, with data obtained from The International Country Risk database, published by The PRS Group, Transparency International and the World Bank, statistical analysis of time series, ordinary least squares, and Granger causality was used. The main result shown by the study is the verification of the hypothesis that corruption is the sand in the wheels since increasing the income from natural resources increases corruption, presenting obstacles such as deviation of public spending and an increase in internal conflicts. Finally, the policy recommendation is to prioritize strategies that improve transparency and governance in the management of natural resources as well as provide technology that helps sustainable and efficient extraction, improving the value chain from extraction to commercialization.